Stage IB2 adenosquamous cervical cancer diagnosed at 19‐weeks' gestation. (3rd December 2014) - Peculis, Luiza D.; Ius, Yvette; Campion, Michael; Friedlander, Michael; Hacker, Neville
<x xml:space="preserve">Abstract</x> Neoadjuvant chemotherapy (NACT) for advanced cervical cancer in pregnancy has been shown to increase operability and be effective against spread of disease. In all reported cases of advanced disease, residual tumour has been found at surgery following NACT. We present a case of a 27‐year old diagnosed with stage IB2 adenosquamous cervical carcinoma at 19‐weeks' gestation who was treated with NACT. Following caesarean section and radical hysterectomy, histopathology showed no evidence of residual tumour in the cervix and negative pelvic lymph nodes.